2013
DOI: 10.1111/ajo.12148
|View full text |Cite
|
Sign up to set email alerts
|

Smoking rates and smoking cessation preferences of pregnant women attending antenatal clinics of two large Australian maternity hospitals

Abstract: Background: Tobacco smoking is the most important preventable cause of many adverse pregnancy outcomes. Some women continue to smoke during pregnancy although the harmful effects are evident. Aims: To characterise pregnant smokers and to understand their smoking behaviours and preferences for smoking cessation. Materials and Methods: Pregnant women (≥18 years) attending the antenatal clinics of two large Victorian maternity hospitals completed a prepiloted questionnaire which included items regarding socio-dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 28 publications
7
28
0
Order By: Relevance
“…[25] In a study performed in 1899 pregnant women, although all of them aware that smoking was harmful during pregnancy, 29% of them still continued to smoke during pregnancy. [26] When physical, and psychological dependency develops towards a substance, these substances make the addict feel good even for a short time. [27] This effect of feeling good may be effective in persistent use of these substances despite their known harmful effects.…”
Section: Discussionmentioning
confidence: 99%
“…[25] In a study performed in 1899 pregnant women, although all of them aware that smoking was harmful during pregnancy, 29% of them still continued to smoke during pregnancy. [26] When physical, and psychological dependency develops towards a substance, these substances make the addict feel good even for a short time. [27] This effect of feeling good may be effective in persistent use of these substances despite their known harmful effects.…”
Section: Discussionmentioning
confidence: 99%
“…Scores on the test range from 0 to 10; a score between 1 and 2 indicates low nicotine dependence, between 3 and 4 low-to-moderate dependence, 5-7 moderate dependence and 8 or more indicate high dependence. Nicotine dependence was assessed using the sum of the FTND and was coded into two levels: low (0-4) and high (5)(6)(7)(8)(9)(10).…”
Section: Smoking Behaviourmentioning
confidence: 99%
“…A systematic review of qualitative studies investigating the psychological and social factors around women attempting to quit smoking during pregnancy demonstrated that women were aware of the health risks for the foetus associated with smoking [6]. However, knowledge of potential health risks was not sufficient to motivate them to quit [6,7]. The findings of Gilman et al sug-gested that nicotine dependence may be the most important health barrier to smoking cessation during pregnancy [8].…”
Section: Introductionmentioning
confidence: 99%
“…While the debate about mechanisms continues, one thing is clear: fetal exposure to smoking is associated consistently with lower socio-economic status. Recent large survey studies from Australia and Canada show smoking in pregnancy to be predicted by being younger, having a smoker in their household, irregular medical care, reporting a mental disorder and lower socio-economic status [14,15]. Leung et al attribute the higher prevalence of exposure to smoking in pregnancy in low SES settings to overcrowding and greater exposure to smoking environments, but the issue is far deeper.…”
Section: Intrauterine Health Inequalitiesmentioning
confidence: 99%
“…Exposure to tobacco smoke in pregnancy is arguably one of the most important preventable causes of a wide range of adverse maternal and child outcomes [15]. These findings on passive smoking have a number of policy and prevention implications: a broader family-based intervention is required; preconception planning is essential; legislation around tobacco control needs to be pushed forward and education and advice for health professionals should be proactive.…”
Section: Policy Implicationsmentioning
confidence: 99%